Analysis of Financing Tools for Science and Technology-based Small and Medium-sized Enterprises - Chen, Sizhuo (Transactions on Economics, Business and Management Research, 2024)
Contemporarily, there has been extensive debate surrounding the challenges of financing and high costs encountered by science and technology-based small and medium-sized enterprises (SMEs). One of the primary factors contributing to this issue is the inadequate alignment between traditional financial models and SMEs. In accordance with the national imperative to vigorously advance new high-quality productive forces, it is of paramount importance to bolster science and technology enterprises as the vanguards of China’s scientific and technological innovation. The seamless integration of finance and technology serves as a potent enabler in realizing this objective. The study examines the mismatch between conventional financial instruments and the specific needs of science and technology-based SMEs, while also delving into the characteristics and viable solutions for investment tools required by such SMEs. It reveals that the future development trajectory of investment tools for technology-based SMEs lies in fostering equity financing through venture capital and promoting bond financing based on light assets. On this basis, it is advocated for robust advancement of an investment-lending linkage mechanism to effectively broaden avenues for financing and strengthen intellectual property protection. This contribution offers valuable insights into shaping the future landscape of financial tools tailored to technology-based SMEs.